Evaluasi Komprehensif in silico Profil ADME Aqneursa dan Miplyffa: Strategi Seleksi Senyawa Baru yang Disetujui FDA untuk Terapi Niemann-Pick Tipe C - Dienna, Annisha Noor; Utri, Chynthia Azhari; Hikmah, Sitti Ainun; Nurbaiti, Novalia (Universitas Negeri Gorontalo, 2026)
Niemann-Pick disease type C (NPC) is a rare neurodegenerative disorder requiring new therapeutic options, where ADME (Absorption, Distribution, Metabolism, Excretion) profiles are critical for drug development. This study aimed to conduct a comparative in silico prediction of the ADME profiles of two novel FDA-approved compounds, Aqneursa and Miplyffa, as candidate therapies for NPC. The result in silico profiling was developed from the web-based tool, SwissADME, such as physicochemical characteristics, lipophilicity, solubility, pharmacokinetics, and drug-likeness. Aqneursa follows all the key drug-likeness rules (Lipinski, Ghose, Veber, Egan, Muegge), has a low molecular weight (173.21 g/mol), a well-soluble, a high gastrointestinal absorption, and a balanced lipophilicity (Log P 0.66). In contrast, Miplyffa presented significant pharmacokinetic challenges, including a high molecular weight (505.90 g/mol), extreme hydrophilicity (Log P -0.21), high polarity (TPSA 202.65 Å²), low GI absorption, and multiple violations of drug-likeness criteria. Although both compounds were predicted to be non-substrates of P-glycoprotein and non-inhibitors of major CYP450 enzymes, neither was predicted to cross the blood-brain barrier (BBB). In conclusion, Aqneursa is good for oral drugs and worthy of further development for NPC, whereas Miplyffa requires alternative formulation strategies or structural modifications.